Understanding historic concrete - Collie, Michael; Bussell, Michael (Distributed by Insight Media, 2010)
Concrete is used more than any other man-made material and the UK has a vast number of concrete structures of varying ages. For the engineer tasked with appraising, repairing or altering a concrete structure, concrete's opacity presents problems with assessing the structure. For example, is the concrete in question mass concrete or reinforced, or even pre-stressed? Perhaps it is not structural at all, merely disguising a steel frame? It is always important to understand what materials you are dealing with. This programme aims to give the engineer a feel for what is likely to be found at different dates and with different types of structures. It is in the form of an interview with Michael Bussell.